Deuterium retention in tungsten studied by sequential implantations at ELM-relevant energies. (March 2023) - Vuoriheimo, T.; Liski, A.; Heinola, K.; Jalkanen, P.; Mizohata, K.; Ahlgren, T.; Räisänen, J.
Highlights: Fuel retention of transient high energy pulses in fusion plasma. Low and high energy deuterium implantations to tungsten. Sequential implantations cause more retention than single energy implantations. Order of sequential implantation matters. Abstract: Plasma edge-localized modes (ELMs) can cause considerable fuel retention in fusion reactor vessel walls by implanting plasma particles with high energies and fluxes. The effect of deuterium ions implanted into tungsten with ELM-relevant energies was studied in laboratory conditions using ion beams. Deuterium implantations were done at room temperature with low fluxes with energies and fluences corresponding to JET and ITER estimates in a single ELM event for both inter-ELM and intra-ELM conditions at the divertor during high power operation. Deuterium implantations with 100 eV/D correspond to an inter-ELM phase, whereas implantations with 5 keV/D or 20 keV/D were used to mimic intra-ELM phases at JET and ITER, respectively. Resulted deuterium retention from these single energy implantations was compared with sequential implantations of low energy – high energy sequences as well as high energy – low energy sequences. Retention was measured by ERDA to obtain the amount of deuterium at the irradiated depth as well as the depth profiles for each implantation. High energy – low energy sequential implantations showed increased retention profile around the implantation-induced damage maximum. In low energy – high energy sequential implantations the observed retention was increased throughout the analyzed depth.